Hegel’s Political Theology of Kenosis: From the Death of God to the Hegelian Monarch - Molina, Almudena (Sophia, 2025)
This article explores the concept of the death of God in Hegel's philosophy and its implications for his political thought. It argues that Hegel's notion of the death of God involves a Christological kenotic sense of self-emptying, which extends beyond his philosophy of religion to impact his entire philosophical system, including politics, given that Hegel considers that the state consists in the march of God. The paper aims to interpret Hegel’s stance on the death of God as kenotic and its integration into his system, with the purpose of addressing how this kenotic structure manifests in concrete conceptions of the state. Specifically, it examines the enigmatic figure of the Hegelian monarch as a kenotic-political figure. Finally, it concludes that Hegel's political thought consists of a political theology of kenosis, which is more concerned with the divestment of power rather than a plenipotentiary paradigm.